PENGARUH KOMUNIKASI SALES PERSON DALAM MEMBANGUN KEPERCAYAAN TERHADAP HUBUNGAN JANGKA PANJANG (Fokus Ekonomi, 2008)
Previous of trust have found that trust was a central role in development of successrelationship This study try to answer that question with monitoring relationship between PT.Combiphar’s salesperson and ritailer in Semarang. In addition to know consequences of trust, theauthor also analyze long-term in relationship as consequences of trust.To answer rhe question on this study, the outhor develops a research model from literaturereview. The model has two hypothesis with variables : communication ability from salesperson,trust to salesperson and long-term relationship. Data analyze to 65 ritailer respondent a number ofdrugstore, haberdasherry, Minimarket and Supermarket from Combiphar product in Semarang andis done using Structural Equation Modeling as analysis toll on AMOS 4.01. program.Result of data analysis showed that all hypotesis can be received. Thus, it can beconcluded that trust to salesperson can be influenced by factors : communication ability fromsalesperson for indicators communication frequencies, dialog communication, verbalcommunication and listening. Furthermore from that trust can be ritailer influences to long-termrelationship with that salesperson.Key words: communication, trust, long term relationship